Rediscovery of Rhyacoglanis pulcher (Boulenger, 1887) (Siluriformes: Pseudopimelodidae), a rare rheophilic bumblebee catfish from Ecuadorian Amazon - Chuctaya Vasquez, Junior Alberto (2023)
Rhyacoglanis pulcher is a rare Neotropical rheophilic bumblebee catfish known only from the type locality in the Cis-Andean Amazon region, Ecuador, and the type-species of the genus. So far, the three syntypes collected in 1880 were the only specimens unambiguously associated to the name R. pulcher available in scientific collections. Recently, a specimen was discovered in a fast-flowing stretch of the Villano river, a tributary of the Curaray river, Napo river basin, Ecuador, representing a new record after nearly 140 years. Here, we pres ent this new record, identified by morphology, provide the DNA barcode sequence of the specimen, and propose why the species of Rhyacoglanis are scarce in zoological collec tions. Additionally, we discuss the intraspecific variation in the color pattern observed in R. pulcher.